Psychiatric Comorbidity and Stress in Medical Students Using Neuroenhancers - Jebrini, Tarek; Manz, Kirsi; Koller, Gabriele; Krause, Daniela; Soyka, Michael; Franke, Andreas G. (Frontiers in Psychiatry, 2021)
Background: Pharmacological neuroenhancement (PN) is a common healthcare problem at least among students. PN seems to be associated with stressful situations. There is a lack of data about personal characteristics, comorbidities and coping strategies regarding stress and factors of resilience in students and medical staff. Methods: A web-based survey about the non-medical use of PN drugs with a focus on neuroenhancement was developed and distributed among medical students throughout Germany; the questionnaire was open in April and May of 2020. The survey contained questions about the use of well-known PN drugs, frequency, special purposes, reasons for the use, psychiatric disorders, use of psychotropic drugs apart from PN purposes and factors of resilience using the brief resilience scale. Results: Data of 1,159 students of medicine were analyzed. The most frequently used substances for PN were coffee (78.8% lifetime prevalence rate), energy drinks (45.7%), caffeine tablets (24.3%), methylphenidate (5.2%), illicit amphetamines (2.0%) and cocaine (1.7%). 98.4% suspected that PN drug use could lead to addiction. PN drug use specifically for PN was significantly associated with the use of a) any psychotropic drug (other than neuroenhancers), b) any psychiatric disorder and c) higher values of feeling pressure to perform in professional/ students´ life and in private life as well as d) the subjective feeling of pressure to perform to be burdening and e) harmful to one´s own health. PN drug use in general was significantly associated with being less resilient. The use of illicit PN drugs, over the counter drugs and prescription drugs was associated with being less resilient. Conclusion: This study indicates that PN with legal and illegal drugs is a widespread phenomenon among German medical students. Users seem to be more often burdened by psychiatric disorders, especially addictive disorders, the perception of stress, pressure to perform and low levels of resilience. These aspects should be considered in further investigation of PN drug use.